2008
DOI: 10.1007/s11999-008-0165-z
|View full text |Cite
|
Sign up to set email alerts
|

Curved-stem Hip Resurfacing

Abstract: Hip resurfacing is an attractive concept because it preserves rather than removes the femoral head and neck. Most early designs had high failure rates, but one unique design had a femoral stem. Because that particular device appeared to have better implant survival, this study assessed the clinical outcome and long-term survivorship of a hip resurfacing prosthesis. Four hundred forty-five patients (561 hips) were retrospectively reviewed after a minimum of 20 years' followup or until death; 23 additional patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…It is possible, however, for a patient to prefer a prosthesis that ultimately does not perform as well as another. In my prior study, all of 27 patients who had an HRA on 1 side and a conventional THA on the other preferred the HRA 15 . Several—but not all—comparison studies have shown HRA to have advantages over THA 3 - 8 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It is possible, however, for a patient to prefer a prosthesis that ultimately does not perform as well as another. In my prior study, all of 27 patients who had an HRA on 1 side and a conventional THA on the other preferred the HRA 15 . Several—but not all—comparison studies have shown HRA to have advantages over THA 3 - 8 .…”
Section: Discussionmentioning
confidence: 95%
“…There are reasons beyond femoral bone conservation for surgeons to consider HRA. There is less stress-shielding of the proximal part of the femur with HRA, since the endosteal medullary surface of the femur is loaded more physiologically 15 , 16 . Complications such as infection and instability can be more difficult to treat after THA 16 .…”
mentioning
confidence: 99%
“…Femoral neck fracture is a rare complication after hip resurfacing, occurring at reported rates of 0% to 7%. Femoral components placed in 5° valgus have a factor of 6.1 reduction in the relative risk of an adverse outcome [ 18 , 19 ]. These findings emphasize that sufficient and careful preoperative planning is essential to improve the outcomes and longevity of surface arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…The acetabular and bipolar polyethylene are from 3.23–3.68 mm in minimum thickness. The acetabular shells are 2 mm thick and the coating for cementless fixation adds another 1 mm ( 13 , 21 , 22 ). The polyethylene bearings are GUR 1020 cross-linked at 7.5 Mrad.…”
Section: Methodsmentioning
confidence: 99%